A Novel LC-APCI-MS/MS Approach for the Trace Analysis of 3,4-Difluoronitrobenzene in Linezolid - Yujin Lim; Aelim Kim; Eunyeong Shin; Hwangeui Cho (Pharmaceuticals)
Background/Objectives: Oxazolidinones are novel antimicrobial agents used to combat bacterial infections, particularly multidrug-resistant strains. However, the synthesis of oxazolidinone derivatives, such as linezolid, often involves the use of 3,4-difluoronitrobenzene (DFNB) as an initiator. Despite its effectiveness, residual DFNB in drug products raises significant health concerns due to its structural similarity to toxic and carcinogenic nitrobenzenes. This contamination is particularly concerning in pharmaceutical formulations, where it poses potential patient safety hazards. Therefore, strict concentration limits for this impurity are necessary. Methods: To ensure tight control of DFNB concentrations, this study established an 8.3 µg/g target limit. An advanced high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed to overcome current limitations in detecting trace DFNB. Under negative atmospheric pressure chemical ionization (APCI) conditions, DFNB exhibited characteristic ion formations, including [M]•− through electron capture and [M − F + O]− via substitution reactions. The quantitative method utilizes MS/MS ion transitions of the substitution product while optimizing chromatographic and spectrometric parameters to enhance both sensitivity and specificity. Conclusions: Validation tests confirm the efficiency, precision, and accuracy of this method, with a low limit of quantification (LOQ) of 5 ng/mL (0.83 µg/g). This technique enables accurate detection and quantification of DFNB in linezolid active pharmaceutical ingredient (API) and various formulations, providing a reliable tool for quality control. This method ensures the safe use of linezolid by effectively monitoring and minimizing the risks associated with DFNB contamination.